SEC publishes final rules amending the rules of practice for administrative proceedings. Issue 4 (7th November 2016) - McKown, Joan; Klehm III, Henry; Gordon, Harold; Woodcock, David; Bradley, Daniel
Abstract : Purpose: To explain and evaluate amendments to the rules of practice governing the US Securities and Exchange Commission's (SEC's) Administrative Proceedings that were adopted by the Commission on July 13, 2016. Design/methodology/approach: Describes SEC's increased pursuit of enforcement actions in APs, criticisms of the AP process, and corrective legislation. Describes the July 2016 amendments covering expansion of the prehearing period, allowance of depositions, timing for completion of document production in discovery phase, required disclosure of affirmative defenses, permitted dispositive motions, and admissibility of hearsay evidence. Assesses the practical impact of the amendments. Makes recommendations concerning advanced preparation for APs, depositions and witness-interview strategies, particular care concerning statements in Wells submission, availability of investigative record to defense counsel, admissibility of hearsay evidence, and defenses based on reliance on counsel. Findings: The amended rules are a step in the right direction but do not fully correct the numerous and severe imbalances that exist in the Commission's administrative enforcement process with respect to the availability of various discovery mechanisms, the timeline for trying a case, and more. Practical implications: Every entity or individual that is involved in an SEC enforcement investigation, or that may become a respondent in an SEC Administrative Proceeding, should take certain practical steps such as those recommended in this article to minimize the structural disadvantages it will face and to maximize the benefits conferred by these latest amendments to the rules of practice. Originality/value: Practical background and guidance from experienced enforcement, litigation, securities and financial services lawyers.